FTIR Spectral Analysis of Chitosan-Lignin Nanocomposites: A Comparative Analysis Before and After Imidazole Functionalization - Khashan, Hussein Sadiq; Al-Deresawi, Tayseer Shamran (American Journal of Biomedicine and Pharmacy, 2025)
In this work, chitosan, lignin, and their nanocomposite are analyzed using Fourier Transform Infrared Spectroscopy (FTIR) both before and after imidazole functionalization. The components' chemical bonds and structural interactions were assessed using FTIR. After composite synthesis and further modification, significant spectral changes and the appearance of additional absorption bands were noted. The findings demonstrated that imidazole groups were successfully conjugated to the chitosan-lignin matrix, increasing the variety of its functional groups and opening up new possibilities for environmental cleanup. The emergence and displacement of important peaks, including aromatic C=C stretching, amide I bands, and O–H/N–H stretching, revealed information on the creation of new covalent bonds and hydrogen bonds. These results confirm FTIR's validity as a trustworthy method for describing molecular interactions in bio-based nanomaterials.